Olfactory loss in poly (acrylonitrile-butadiene-styrene) plastic injection-moulding workers - Cheng, S.-F. (Occupational medicine (Oxford), 2004)
Plastics manufacturing factories are the fifth largest category of factories in industrial estates in Taiwan. It is known that complex airborne compounds and pungent odours are emitted during plastic injection-moulding processes. Workers exposed to acrylonitrile-butadiene-styrene (ABS) thermal decomposition products (TDP) may have olfactory loss. This study examined olfactory loss in injection-moulding workers exposed to ABS TDP. The method recommended by the Connecticut Chemosensory Clinical Research Center (CCCRC) was used to test the olfactory function of subjects, including 1-butanol threshold and odour identification, both pre- and post-work. The study sample included 52 ABS plastic injection-moulding workers (exposed group), as well as 72 workers from other departments (reference group). The results revealed that the exposed group had lower olfactory function after work than the reference group. The decrease in olfactory function after 1 workday was statistically significant. The prevalence of abnormal olfactory function post-work in the exposed group was higher than in the reference group. The findings of this study implied the ABS plastic injection-moulding process may worsen olfactory function among workers. Notably, this effect decreased olfactory threshold scores, not odour identification scores.